2003
DOI: 10.4049/jimmunol.171.1.489
|View full text |Cite
|
Sign up to set email alerts
|

Short Term Administration of Costimulatory Blockade and Cyclophosphamide Induces Remission of Systemic Lupus Erythematosus Nephritis in NZB/W F1 Mice by a Mechanism Downstream of Renal Immune Complex Deposition

Abstract: NZB/W F1 mice with established nephritis were treated with a single dose of cyclophosphamide with or without a 2-wk course of murine CTLA4Ig, either alone or in combination with anti-CD154. Sixty to 80% of treated mice entered remission, and remission could be reinduced following relapse. A decrease in the frequency of anti-DNA-producing B cells and activated T cells was observed in treated mice, but this effect lasted only 3–6 wk, while remissions were sustained for up to 20 wk. Light microscopy of the kidney… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
113
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(123 citation statements)
references
References 41 publications
8
113
1
Order By: Relevance
“…This indicates that cyto-and chemokines are involved in the development of LN. Of interest, CXCL13 was one of only two chemokines (of 61 tested inflammatory chemo-and cytokines) up-regulated at the mRNA-level in this experimental model for SLE before glomerular or interstitial infiltration was evident, but early immune complex deposition occurred [35]. These findings support the hypothesis that there is an ordered progression of inflammatory invasion in LN and that CXCL13 is a distinctive early event in the development of LN.…”
Section: Cd11csupporting
confidence: 75%
“…This indicates that cyto-and chemokines are involved in the development of LN. Of interest, CXCL13 was one of only two chemokines (of 61 tested inflammatory chemo-and cytokines) up-regulated at the mRNA-level in this experimental model for SLE before glomerular or interstitial infiltration was evident, but early immune complex deposition occurred [35]. These findings support the hypothesis that there is an ordered progression of inflammatory invasion in LN and that CXCL13 is a distinctive early event in the development of LN.…”
Section: Cd11csupporting
confidence: 75%
“…Table III summarizes our findings in relation to what has been published regarding the treatment of lupus erythematosus in NZB/W F1 mice. To our knowledge, only the use of CTLA4Ig in combination with cyclophosphamide (CTX) (15,32) and administration of C-reactive protein (16) have demonstrated a reversal of defined high grade proteinuria with $300 mg/dl. However, a median survival of 73 wk in NZB/W F1-treated mice with established disease as seen in our experiments has not been described before.…”
Section: Discussionmentioning
confidence: 99%
“…The second type of study focusing on established disease initiated treatment from a defined highgrade proteinuria (grade 3+ and 4+ with at least $300 mg/dl), which requires individual treatment schedules for each mouse. Although this study design most likely reflects the clinical situation with patients with lupus, only a few of them exist (14)(15)(16).…”
mentioning
confidence: 99%
“…This injury has been attributed to the induction of an immunopathology resulting from immune complex (IC) deposition (1)(2)(3)(4)(5)(6)(7). However, it is also clear that IC by itself is not sufficient for the development of glomerular injury (8)(9)(10)(11) and that CD4 T cells also contribute to the glomerular injury seen in SLE. Wofsy et al (12)(13)(14) and Jabs et al (15) showed that anti-CD4 T cell Ab therapy could significantly reduce the frequency and the extent of glomerulonephritis in both NZB/W F 1 and MRL/lpr mouse models of lupus.…”
mentioning
confidence: 99%